THE THICKNESS OF THE RETINAL GANGLION CELLS COMPLEX (GCC) AND NERVE FIBERS IN THE MACULAR AREA IN PATIENTS WITH PRIMARY OPEN-ANGLE GLAUCOMA (POAG) THAT RECEIVED L-ARGININE IN TERMS OF THEIR TREATMENT - Gonchar' E. N. (Ukrainian Society of Ophthalmologists, 2015)
Introduction. In accordance with the contemporary concept, the nature of the glaucomatous damage lies in the accelerated loss of retinal ganglion cells and their axons as optic nerve components, which is associated with the neurons neurotrophic defense reduction, the breach of encephalitic trophic factors transportation to the retinal ganglion cells, as well as with neuroglia involvement, which ensures the optic nerve nutrition. Objective: the study of the thickness of the retinal ganglion cells complex (GCC) and nerve fibers in the macular area in patients with primary open-angle glaucoma (POAG), which received L-arginine in terms of their treatment. Material and Methods: 109 patients (192 eyes) with POAG were examined in terms of the study. The patients' age ranged from 40 to 87 years. All patients were randomized into two groups: index treatment group and control group. The index group consisted of 60 patients (102 eyes) with POAG, which received L-arginine treatment along with the background therapy (in accordance with our own proposed scheme ? UA 52177 U Ukrainian patent license). The control group consisted of 49 patients (90 eyes) with POAG that received the background therapy. The examination included conventional ophthalmic examination techniques, as well as static computer perimetrium and optical coherence tomography (OCT). Results: It has been established that in patients with POAG that received L-arginine in their treatment, the long-term period stabilization frequency of the nerve fibers average thickness in the macular area was 16% higher than that of the control group (71.6% and 55.6%, respectively), the stabilization frequency of the retinal ganglion cells complex (GCC) average thickness was 23.1% higher than that of the control group (85.3% and 62.2%, respectively), the stabilization frequency of retinal ganglion cells complex (GCC) average thickness in the lower part was 24.6% higher than that of the control group (82.4% and 57.8%, respectively), and the differences were reliable for all parameters (p<0.05). Conclusion: The L-arginine use in the treatment of patients with POAG (primary open-angle glaucoma) contributes to the long-term period stabilization of retinal ganglion cells complex (GCC) average thickness, as well as its thickness in the lower part and the macular area nerve fibers thickness.